Analysis and Implications of the Results of a Teacher Leader’s Pedagogical Practices in a Pilot Test on Innovation in Conectándonos Project - Baltodano-Enríquez, Manuel (2018)
This article presents the results of a teacher leader’s pedagogical practices in a pilot test on innovation implemented in a Costa Rican primary school. The pilot test was conducted due to the need of renewing the technological equipment in schools belonging to Conectándonos MEP-FQT project run by the Department of Research, Development, and Implementation of the Ministry of Public Education and Quiros-Tanzi Foundation. This pilot test aimed to diagnose the pedagogical practices of a teacher leader through the exploration and use of didactic digital resources of Clamshell-type laptops and an interactive projector. This equipment was used to favor the teacher’s pedagogical mediation through the access, selection, and use of didactic digital resources. To collect the information, we used non-participant observation guides, a questionnaire with open questions, and a bibliographic review of the teacher’s didactic planning. The systematization of the observation guides permitted to put in evidence, naturally and concretely, the aspects covered by the objectives of the study. The information was analyzed with a qualitative approach of phenomenological type. This approach defined categories and subcategories that, later, were linked to establish coincidences, similarities, differences, and the presence or absence of terms and phrases. Likewise, the data were interpreted to relate the information collected through the analysis and the theoretical patterns. This interpretation permitted, afterwards, to reflect on the studied categories. Finally, the main conclusion drawn from the pilot test was that the collaborative work between students was promoted and the learning objectives in the didactic planning drawn up by the teacher were achieved.